Treatment of Cleft lip & Palate Related Maxillary Hypoplasia with RED System: Case Report - Hakan El; Selçuk V. Çınar; İlken Kocadereli; Emin M. Mavili (Galenos Yayinevi, 2009)
Clefts of the lip and palate present one of the most challenging congenital disorders to the orthodontists and craniofacial surgeons. A common finding is maxillary hypoplasia. Current case report presents the treatment of a 19 years old female unilateral cleft lip and palate patient characterized with maxillary constriction, retrusion and severe underjet. The case has been successfully treated with fixed appliance therapy and rigid external distraction and relapse at the end of treatment is minimal. However, longer follow-ups are required to assess the exact amount of stability.